The Impact of Assessment and Selfassessment Methods of Learning Achievements and Progress on Adolescent Self-esteem Building - Meškauskienė, Asta; Guoba, Andrius (Pedagogika, 2016)
Assessment is meaningful when it motivates to learn and is perceived as the progress made by student in the process of learning, which strengthens students’ self-esteem. The school insufficiently focuses on individual learning needs of students and allocates the most significant attention to testing. Such system of assessment fails to address the set goals of education and does not comply with contemporary methods of teaching/learning. The purpose of study is to reveal teachers’ attitude towards formal and non-formal ways of assessing learners’ achievements that boost or impair their self-esteem. The teachers emphasised the necessity to concentrate on assessment providing learners with efficient feedback, which indicates guidelines for improvement and enhances their self-esteem. Assessment should be treated as support to a learner, which enables him or her to adequately evaluate own abilities and opportunities, motivates to seek progress.